2009
DOI: 10.1203/pdr.0b013e318193f134
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Reduces Vagal Baroreflex Sensitivity in the Late Gestation Fetus

Abstract: Goals to understand the etiology of essential hypertension have proposed that this problem arises, in part, because of changes within brainstem circuits involved in arterial blood pressure (ABP) control. It has been suggested that nitric oxide (NO) exerts inhibitory influences on the integration of afferent discharge from the arterial baroreceptors. This study tested the hypothesis that the inhibitory influence of NO on the arterial baroreflex is present in fetal life. Fetal baroreflex sensitivity was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…For instance, it is known that baroreception can be depressed by oxidative stress 48 and by NO. 49, 50 Similarly, oxidant tone and NO within the medulla can alter sympathetic and vagal outflow. 51,52 Whilst systemic administration of vitamin C increases baroreflex sensitivity in the adult, 53 probably via actions on carotid baroreceptors, 48 acute intraventricular administration of vitamin C has been shown to depress baroreflex gain through enhancements of parasympathetic outflow at the level of the NTS and/or nucleus ambiguous.…”
Section: Hrv and Baroreflex Functionmentioning
confidence: 99%
“…For instance, it is known that baroreception can be depressed by oxidative stress 48 and by NO. 49, 50 Similarly, oxidant tone and NO within the medulla can alter sympathetic and vagal outflow. 51,52 Whilst systemic administration of vitamin C increases baroreflex sensitivity in the adult, 53 probably via actions on carotid baroreceptors, 48 acute intraventricular administration of vitamin C has been shown to depress baroreflex gain through enhancements of parasympathetic outflow at the level of the NTS and/or nucleus ambiguous.…”
Section: Hrv and Baroreflex Functionmentioning
confidence: 99%
“…More recently, the contribution to these responses of local agents, in particular NO, independent of neuroendocrine control has gathered increasing attention (Morrison et al 2003; Thakor & Giussani, 2009; Thakor et al 2010 b ). Studies have shown that fetal NO bioavailability can increase during acute hypoxia, altering neuroendocrine constrictor influences and metabolic responses (Morrison et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory influence of NO on the arterial baroreflex is present in fetal life. The gradient of the pulse interval-arterial BP relationship was nearly doubled during the NOS blockade in fetal sheep, demonstrating that NO attenuates the sensitivity of the cardiac baroreflex during fetal life and that NO exerts inhibitory influences on the integration of afferent discharge from the arterial baroreceptors [37]. Hypertension and bradycardia could either derive from the independent effects of LNAME on vascular tone and HR, from baroreflex interaction, or from a combination thereof.…”
Section: Discussionmentioning
confidence: 94%